Constitutional and legal status of a student as a subject of educational law: between public and private legal regulation - Dikhtiaruk, A. B. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The scientific article provides a comprehensive constitutional and legal analysis of the status of a student as a subject of educational law. It is established that the legal status of a student has a dual nature, as it combines elements of public-law regulation with features of private-law contractual obligations. It is argued that modern educational law should perceive the student not merely as a recipient of educational services, but as an equal partner engaged in shaping the content of educational programs, their evaluation, and quality assurance. This approach necessitates an update of the regulatory mechanisms governing students’ rights and obligations towards a clear definition of institutional guarantees, procedural fairness, and legal certainty in interactions between the student and the higher education institution’s administration. The article structures the student’s legal status along three dimensions: normative-legal, sociocultural, and institutional. The normative-legal dimension encompasses the rights and duties enshrined in laws and subordinate acts. The sociocultural dimension is manifested through the student’s engagement in shaping the academic environment, while the institutional dimension is reflected in mechanisms for student participation in university governance and student self-government. In summary, the public-law dimension of the realization of educational rights is ensured through the imperatives of the Constitution of Ukraine, sectoral legislation, and internal university regulations, which shape the student’s legal status by defining their rights, duties, guarantees of participation in the management of the educational process, and mechanisms for redress in case of rights violations. Ultimately, the legal status of the student is viewed as a dynamic legal construct that requires ongoing transformation and adaptation to changes in the sphere of higher education. Emphasis is placed on the need to strengthen the actual mechanisms for guaranteeing and protecting students’ educational rights, enhance the effectiveness of judicial and internal control, ensure transparency in public administration and contractual relations, and enshrine legal certainty in the interaction between the student and the higher education institution as equal participants in the educational process.